2023
DOI: 10.1002/adem.202201801
|View full text |Cite
|
Sign up to set email alerts
|

Improved Antifouling Ability for Double‐Network Hydrogel Coatings with Excellent Elastic and Toughness under Marine Tidal Environment

Abstract: The marine coating in the tidal zone is crucial to restoring its protective function in the case of coating defects, mainly due to the structural damage of the coating by the alternation of wet and dry in the tidal zone and the surface damage of the coating by the impact of sand and gravel. Hydrophilic materials such as hydrogel transformed the tidal zone into an entire immersion zone. Due to the complexation of copper, the fouling problem can be effectively reduced. The coating (AAm/Alginate‐Ca/Cu‐BTA) has ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Figure 8 shows the production process of the A-H DL coating. The copolymerization of AAm and TMSPMA resulted in the formation of the first network of hydrogels, establishing the initial anchoring with the primer [16,20,24]. Incorporating the gel microspheres, prepared as per the aforementioned steps, into the gel precursor enabled the creation of a second network of hydrogels.…”
Section: Preparation Of A-h DLmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 shows the production process of the A-H DL coating. The copolymerization of AAm and TMSPMA resulted in the formation of the first network of hydrogels, establishing the initial anchoring with the primer [16,20,24]. Incorporating the gel microspheres, prepared as per the aforementioned steps, into the gel precursor enabled the creation of a second network of hydrogels.…”
Section: Preparation Of A-h DLmentioning
confidence: 99%
“…Considering the application scenarios of hydrogel marine coatings, dual-network hydrogels prove particularly well-suited [16,[19][20][21][22][23]. They ensure the stability of the gel coatings over extended periods, even under diverse underwater conditions, thereby offering prolonged protection to the substrate [24].…”
Section: Introductionmentioning
confidence: 99%
“…The initial stage of fouling involves the adhesion of proteins and polysaccharides on materials. Recent studies have highlighted the potent inhibitory effect of hydrogel materials on the adsorption of proteins, polysaccharides, and marine organisms. , Hydrogel coatings, therefore, hold considerable research importance and promise for practical applications in preventing or mitigating marine biofouling at its source.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogel, consisting of a porous polymer material, was chosen in this study due to its excellent antifouling properties. For example, it has been demonstrated that the amphiphilic hydrogel coating had outstanding resistance against the fouling of bacteria, proteins, and other microorganisms under both laboratory and field tests . Li et al designed double-network hydrogel coating loading corrosion inhibitors, which exhibited synchronously good anticorrosion and antifouling properties. However, traditional hydrogel layers generally do not contain biocide, and they always have poor mechanical durability and low adhesion strength with metals .…”
Section: Introductionmentioning
confidence: 99%